P567 Factors influencing gay and queer men's acceptability of integrating substance use care within sexual healthcare settings. (14th July 2019) - Mniszak, Caroline; Parent, Natasha; Carson, Anna; Stehr, Rodney; Ferlatte, Olivier; Knight, Rod
Abstract : Background: Just as sexual health services do not always attend to the substance-related needs of individuals, substance use care tends to neglect sexuality and sexual health. The objective of this study was to identify factors influencing the acceptability of integrating substance use care within sexual health services for young gay, bisexual and other men who have sex with men (gbMSM) – a population that experiences disproportionate drug- and sexual-related harms. Methods: We draw on data from in-depth, semi-structured interviews conducted with 50 young gbMSM (18–30) who use substances during sex in Vancouver, BC. Results: Participants reported infrequently receiving substance use-related care when accessing sexual health services resulting in many having unmet needs surrounding their use of substances during sex. More so, a majority felt unable to initiate discussions about substances with a sexual health provider. Participants described several features of clinical interactions that they felt would enhance their comfort and ability to discuss their substance use, including: (i) the provision of convenient spaces where they could discuss their sexual health and substance use concurrently; (ii) the knowledge that discussions about substance use would be non-judgemental and include a harm reduction approach; and (iii) be offered by knowledgeable, resourceful professionals familiar with the sexualized use of substances among gbMSM (i.e., chemsex; other sub-cultures where substance use occurs). Finally, participants emphasized that mental health interplays with sexual health and substance use and, therefore, represents a key co-occurring health condition that they wanted to feature within discussions about their sexual health and substance use. Conclusion: Findings indicate that young gbMSM who use substances would both benefit from and desire opportunities to discuss substance use within sexual health care settings. Future efforts to more fulsomely integrate the provision of substance use and mental health care for young gbMSM in sexual health care settings are needed. Disclosure: No significant relationships.